Tackling racism in sports psychiatry - Dan Begel (Hogrefe AG, 2023)
Abstract: Racism is embedded in society and, therefore, in sports. This paper summarizes the long history of racism directed at Black athletes in the United States, the various ways that racism is manifest in sports, and the psychological impact of racism on individual athletes. Suggestions for addressing racism in the clinical setting as well as in the athletic environment are presented, along with several clinical vignettes. Because racism affects everyone, it is suggested that clinicians advance their self-awareness and knowledge of the problem, and several avenues for doing so are presented. It is suggested, in addition, that the topic of race be included in the therapeutic agenda while keeping in mind that it is the patient's prerogative to determine when race is relevant and when it is not.